Security policy of India; Modi doctrine - Singh, Col. Dr. Narendra (New Delhi Pentagon Press, 2017)
Our generation is blessed with unique Leader, Narendra Damodardas Modi who embodies both tremendous faith in Indian people and desire to take India forward in community of nations. Whether dealing with Chinese President Xi on the Border Issue and trade, or the Japanese Prime Minister Abe, or strategic opening of Chahabar, Act East policy, The Cultural circuit and many Modi was articulate to emphasize India. He brought India policy from Utopian dreams to `real politik$1 (B. Narendra Modi has brought to the fore the Kingship, and has emphasised that it has to be discovered and not declared. It is a question that must be answered as best as one can for the prosperity of the people in recognition that it will remain open to debate; that his decision will be judged by whether the greatest, most consequential issues faced, and the decisions taken to meet these challenges before it is possible to see what the outcome may be. Modi has changed the very manner in which Indian community thought about nation, and national security. Modi by his articulation of Security Policy has brought India to the fore. From hard power Modi has moved the nation to `smart power$1 (B.s
Keywords: Security Sector; National Security; Security Policy; Security-Modi Doctrine